Prothrombin Levels in Serum - Penner, John A (Thrombosis and Haemostasis, 1963)
Prothrombin has been studied in clotting blood and plasma using the modified 2-stage prothrombin assay of Ware and Seegers. The quantity as well as the rate of prothrombin activation has been determined in whole blood and recalcified plasma obtained from 20 normal individuals. A thorough evaluation was made of the techniques used and the effect of variables such as temperature, surface contact, calcium, platelet concentration, and pH.A relatively constant rate of prothrombin activation was observed in clotting blood and recalcified frozen-thawed plasma.The results of this study confirm previous investigations of Langdell, Graham, and Brinkhous using the prothrombin utilization assay. In normal blood, the plasma procoagulants are found to be present in relative excess in comparison to platelet Factor 3. The lack of available platelet factor contained in the intact platelets effectively limits prothrombin activation. Disruption or alteration of the platelets permits the release of large quantities of platelet Factor 3 and produces a marked increase in the rate of prothrombin activation.Glass contact was observed to increase prothrombin activation in blood and plasma.The use of plasma prothrombin as a substrate for evaluation of procoagulant activity is discussed and advantages of this system of assay are emphasized.